(untitled) (Singaporean Journal of Business Economics and Management, 2020)
The study investigated ecopreneurship practices and their effect on innovative performances of selected agro-allied businesses in Nigeria. The study used primary and secondary data. The primary data consist of a structured questionnaire in a five-point Likert scale format administered to three hundred and forty (340) respondents, comprising of owners/managers of agro-allied businesses in North-central, Nigeria that were randomly selected representing the target population of the study. While the secondary data comprised of information sourced from records of institutions in the agriculture sector among the agro-allied owners and managers, as well as from published sources. The data was analyzed using Statistical Packages for Social Sciences as well as Ztest to test the formulated null hypothesis. The findings revealed that ecopreneurial practices have significant influences on the competitive advantage of agro-allied businesses in North Central Nigeria. The study recommends among other things; that the Nigeria government should strengthen its external relations towards establishing national standards for the quality of the environment and the implementation of the environmental regulations. They should take further proactive measures through state-level ministries of environment to encourage the ecopreneurs to develop more environmentally friendly products and as well as enhance their level of involvement in a green production practice